Preparation method of high-gradient porous metal film
By using porous metal support membrane tube and mold forming process in the preparation of porous metal films, the transition bonding layers of metal powder with different particle sizes are filled, and the problem of low mechanical strength and filtration accuracy of gradient porous metal films is solved, achieving high efficiency filtration performance and simple preparation process.
Patent Information
- Application Number
- CN202411553835.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art has problems such as low mechanical strength, low filtration accuracy, large mass transfer resistance and complex process when preparing gradient porous metal films, which limit its application in complex filtration processes.
Using porous metal supporting membrane tubes as internal support, combined with mold forming process, a transition bonding layer composed of metal powder or metal powder coating film paste of different particle sizes is filled between the porous metal outer membrane embryo and the internal supporting metal membrane tubes. , achieve bonding through high-temperature heat treatment, reduce mass transfer resistance and improve filtration accuracy and mechanical strength.
The prepared high-gradient porous metal film has high mechanical strength, filtration accuracy, flux and good permeability. It is suitable for separation processes in complex filtration systems, and has a simple process, low cost and high yield.
Smart Images

Figure CN119281131A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of membrane material preparation, and in particular relates to a method for preparing a high-gradient porous metal membrane. Background Art
[0002] Membrane filtration technology has rapidly emerged in the fields of new biochemical materials, medicine, food, petroleum, etc., and has been continuously developing in the direction of high purity, high precision and high quality, which has provided huge market conditions for the development of membrane materials today. Commonly used membrane materials are divided into inorganic membranes and organic membranes according to their materials. In the early days, organic membranes were widely used, but they had problems such as low mechanical strength, poor corrosion resistance and poor high temperature resistance, and now they cannot meet the growing needs of new industries. Compared with organic membranes, inorganic membranes have developed rapidly in recent years, with advantages such as high temperature and high pressure resistance, corrosion resistance, stable structure and easy regeneration and cleaning. Currently, commonly used inorganic membranes include metal membranes and ceramic membranes. Although ceramic membranes have obvious advantages in strength and corrosion resistance, the inherent brittleness of ceramic materials makes them easy to damage during use and difficult to weld, so the connection and sealing of membrane components are difficult. Compared with ceramic membranes, metal membranes are significantly better than ceramic membranes in mechanical strength and welding performance, and metal membranes are particularly widely used in chemical and pharmaceutical filtration sections.
[0003] In the industrial application process of metal membranes, it is necessary to focus on the filtration accuracy, mass transfer resistance, mechanical strength, etc. of the membrane. In order to improve the filtration accuracy of the membrane, the pore size needs to be reduced, and reducing the pore size will increase the mass transfer resistance, while reducing the mass transfer resistance by reducing the membrane thickness will reduce the mechanical strength of the membrane. At present, technicians reduce the pore size by loading a layer of small-pore metal membrane on the surface of the membrane substrate. Although this method can improve the filtration accuracy of the membrane while hardly affecting the mass transfer resistance, on the one hand, the small-particle metal powder will block the pores of the membrane tube, and on the other hand, the membrane layer has poor bonding strength, and the membrane layer is prone to cracking, falling off and surface defects. In addition, when the size is small and the thickness is thin, the mechanical strength of the membrane material will be restricted, limiting the application of metal membranes. In order to expand the application field of metal membranes, the preparation of new porous metal membrane materials with small pores, high filtration accuracy and high mechanical strength has attracted widespread attention from domestic and foreign researchers. Patent CN103691329A provides a method for preparing a porous stainless steel membrane, firstly, a large-particle stainless steel powder with a low-melting-point metal layer wrapped on the surface is pressed and formed by a powder tablet press, and then a stainless steel powder film layer is prepared on the formed blank, and a highly asymmetric porous stainless steel membrane is finally obtained by sintering. This method can reduce the sintering temperature of the membrane, co-sinter the membrane layer with the substrate, and effectively prevent the membrane layer from falling off. However, when a stainless steel coating is prepared by using metal salts and stainless steel powder together, other impurities are contained in the membrane, which affects the performance of the membrane. Patent CN101428346A provides a method for preparing a stainless steel porous tube with a gradual aperture, wherein stainless steel powders of different particle sizes are mixed with a certain polyvinyl alcohol solution, and a stainless steel powder suspension is prepared, and a stainless steel porous tube with a gradual aperture gradient is prepared by a centrifugal forming method. This method solves the problems of multiple coatings and sintering costs, but there are differences in the sintering temperatures of stainless steel powders of different particle sizes. When stainless steel powders with large particle size differences are sintered at one time, it is difficult to ensure that the material is fully sintered. Patent CN109876667A stainless steel membrane preparation adopts sol-gel method to coat the surface of porous stainless steel substrate, and obtains porous stainless steel membrane after sintering. The pore size distribution of the membrane layer prepared by the sol-gel method is narrow, and the adhesion of the membrane layer on the substrate surface is high. However, its process is relatively complicated, and a series of operations such as polishing, grinding, and pickling of the stainless steel substrate are required. And when the sol solution is applied to the surface of the stainless steel substrate, the small particle size powder in the sol solution will block the substrate pores and affect the membrane performance. Patent CN116328557 discloses a tubular porous metal membrane and its preparation method, using a metal mesh as a raw material, and rolling the metal mesh into a compact tubular structure through a thin plate rolling machine, and then using the cathode electrodeposition of metal single substance to anchor the mesh surfaces to obtain a tubular precursor membrane; finally, the precursor membrane is sintered at high temperature to obtain a tubular porous metal membrane.The metal film prepared by this method has high mechanical strength and high filtering accuracy. Since the metal mesh itself has high mechanical strength, the connection between the metal mesh layers is anchored by electro-deposition of metal elements, and the bonding force between the metal mesh surfaces is further enhanced by high-temperature sintering. However, the electro-deposition of metal elements has the problems of difficulty in controlling the position of precipitation, poor repeatability, large generated metal particles, low uniformity, etc., so the prepared membrane material has poor uniformity and low process repeatability. Patent CN106390763A provides a method for preparing a stainless steel filter membrane tube, firstly mixing three kinds of mixed stainless steel powder with resin powder, placing stainless steel fiber felt in a forming mold, fixing the core rod, and then charging the mixed stainless steel powder to form, and preparing a stainless steel filter membrane tube after pressing, forming and sintering. The stainless steel filter membrane tube prepared by this method has good filtering performance and large flux, and the stainless steel fiber felt placed in the mold can play a role in fixing and assisting in forming, and effectively prevents the stainless steel filter membrane tube from cracking and peeling during the sintering process. However, the sintering temperatures of the three stainless steel powders with different particle sizes are significantly different, making it difficult to achieve effective sintering; and resin powder needs to be added to the stainless steel powder, and the residue after sintering the resin powder will affect the membrane performance. In general, there are many problems with the current method of preparing gradient porous metal membranes, which limits its application in complex filtration processes. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a high-gradient porous metal membrane with a simple preparation process, high yield and cost saving. The prepared high-gradient porous metal membrane has high mechanical strength, high membrane layer precision, high flux and good performance, and is fully suitable for separation processes in complex filtration systems.
[0005] The solution of the present invention is: by using a porous metal support film tube as an internal support, the mechanical strength of the metal film can be effectively improved; then using the mold forming process, a transition bonding layer composed of two metal powders of different particle sizes or metal powder coating slurry is added between the cavity formed by the porous metal outer film embryo and the porous internal support metal film tube. During high-temperature heat treatment, the metal powder with a small particle size has a low melting point, melts and wraps the metal powder with a large particle size, and bonds with the metal powder particles on the surface of the porous metal outer film embryo and the porous internal support metal film tube, with high bonding strength; in addition, the metal powder with a small particle size is consistent with the porous metal outer film powder, which can effectively avoid the difference in thermal coefficient. The preparation process of the present invention does not need to brush or plug the hole on the surface of the support body to increase the transition layer, which can effectively reduce the mass transfer resistance and improve the pore gradient and filtration accuracy of the metal film. The present invention uses quartz tubes and soft rubber sleeves as mold-assisted molding, which, on the one hand, play a role in fixing and assisting molding, and on the other hand, can reduce the fluidity of the metal powder during the sintering process, improve the film forming property of the film layer, and ensure the repeatability and yield rate of the high-gradient metal film. Sintering of metal powder will cause sintering shrinkage. The above-mentioned sintering process can keep the position of the metal powder relatively fixed, so a high porosity can be retained, making the metal film layer have better permeability. In the preparation process, the present invention uses isostatic pressing to press the film layer embryo, which can improve the bonding force between the film layer particles, avoid void defects in the film layer, and improve the strength of the film layer and the flatness of the surface. The porous metal film prepared by the present invention has a high pore gradient, high filtration accuracy, high mechanical strength, and good permeability.
[0006] The specific technical solution adopted by the present invention is as follows:
[0007] A method for preparing a high-gradient porous metal film, characterized in that the high-gradient porous metal film is prepared from metal powder as raw material through a sol coating process, isostatic pressing, mold forming and high-temperature sintering process, and the specific steps are as follows:
[0008] Step 1: prepare a soft rubber sleeve, put the soft rubber sleeve into a quartz tube 1 with a plugging piece at the bottom, form a cavity 1 between the outer wall of the soft rubber sleeve and the inner wall of the quartz tube 1, fill the cavity 1 with metal powder A, and after packaging and isostatic pressing, perform high-temperature heat treatment to prepare an internal support metal film tube;
[0009] Step 2: Using metal powder B as a raw material, mix it with organic additive 1 in proportion to prepare a sol coating liquid B, first apply the sol coating liquid on the inner wall of the quartz tube 2 to obtain a porous metal outer film blank B after drying, and then package the porous metal outer film blank B and perform isostatic pressing treatment;
[0010] Step 3: Place the internal support metal film tube prepared in step 1 into the porous metal outer film blank B that has been isostatically pressed in step 2, and set a plugging piece at one end of the porous metal outer film blank B, forming a cavity 2 between the outer wall of the internal support metal film tube and the inner wall of the porous metal outer film blank B, fill the cavity 2 with metal powder C or metal powder C coating slurry, and set another plugging piece at the other end of the porous metal outer film blank B, thereby forming a high-gradient porous metal film assembly blank;
[0011] Step 4: The high gradient metal membrane assembly embryo prepared in step 3 is subjected to heat treatment under protective atmosphere conditions to obtain a high gradient porous metal membrane.
[0012] Specifically, the metal powder A in step 1 is a stainless steel powder, a nickel alloy powder or a titanium alloy powder with an average particle size of 50 to 200 μm; the inner diameter of the quartz tube 1 is 8 to 49.5 mm. The wall thickness of the internal support metal film tube is 0.2 to 2 mm, the porosity is 30 to 50%, and the average pore size is 4.6 to 19.3 μm.
[0013] Specifically, the isostatic pressing pressure in step 1 is 100-300 MPa, and the holding time is 0-3600 s; the high-temperature heat treatment is carried out under vacuum or reducing atmosphere at 1100-1400° C. for 0.5-5 h.
[0014] Specifically, the material of the metal powder B in step 2 is stainless steel powder, nickel alloy powder or titanium alloy powder; the average particle size of the metal powder B is in the range of 1 to 20 μm.
[0015] Specifically, the organic additive 1 in step 2 is a mixed solution of an organic additive and water; the organic additive is hydroxyethyl methyl cellulose, carboxymethyl cellulose, polyacrylic acid lactone or polyethylene glycol; the mass fraction of the organic additive in the organic additive 1 is 1% to 5%.
[0016] Specifically, the mass ratio of the metal powder B and the organic additive 1 described in step 2 is (0.5-6):1; the inner diameter of the quartz tube 2 is 10-50 mm; the pressure of the isostatic pressing treatment is 100-300 MPa, and the holding time is 0-3600 s. The present invention evenly disperses the metal powder B into the organic additive 1 to form a low-viscosity sol coating liquid, and coats the inner wall of the quartz tube. The formed porous metal outer film blank has high adhesion to the quartz tube, which is convenient for the subsequent preparation process. The present invention improves the bonding force between the film particles through isostatic pressing treatment, improves the film strength and surface smoothness, and avoids the occurrence of void defects in the film.
[0017] Specifically, the metal powder C described in step 3 is mixed by metal powder B and metal powder D in a mass ratio of (0.2 to 5): 1; the average particle size of the metal powder D is 5 to 30 μm; the materials of the metal powder B and the metal powder D are both stainless steel powder, nickel alloy powder or titanium alloy powder; the average particle size of the metal powder B is 1 to 20 μm.
[0018] The present invention fills a transition bonding layer between the porous metal outer film blank and the internal supporting metal film tube. By adding the transition bonding layer, the bonding of metal powder particles between the porous metal outer film blank and the internal supporting metal film tube can be promoted, the bonding force between the film layers is high, and it plays a role of fixing and buffering. Wherein, the transition bonding layer is composed of two metal powders or metal powder coating slurries with different particle sizes; and the metal powder with a small particle size is consistent with the material and particle size of the metal powder used to prepare the porous metal outer film blank, which alleviates the thermal mismatch phenomenon caused by the mismatch of thermal expansion coefficients between metal powders of different particle sizes, can reduce the difference in thermal coefficients, and is conducive to the connection between the outer film porous metal outer film blank and the internal supporting metal film tube; in addition, during sintering, the melting temperature of the metal powder with a small particle size is low, and the metal powder with a large particle size is melted and wrapped, while reducing the sintering temperature, it can achieve effective bonding with the internal supporting metal film tube with a large particle size, and the bonding force between the film layers is high, and a porous metal film with a high gradient is prepared.
[0019] In the present invention, the pore size of the internal supporting metal membrane tube is much larger than the particle size of the filled transition bonding layer metal powder, so that the transition bonding layer metal powder can be smoothly stored in the pores of the internal supporting metal membrane tube, and metal diffusion sintering occurs with the internal supporting metal membrane tube during the sintering process, and the bonding strength between the metal membrane layers is high.
[0020] Specifically, the metal powder C coating slurry described in step 3 is a coating slurry obtained by mixing metal powder C and organic additive 2 in a mass ratio of (1 to 3): 1; the organic additive 2 is a mixture of polyvinyl alcohol, methyl cellulose or polyvinyl pyrrolidone and water; the mass fraction of the organic additive in the organic additive 2 is 1% to 10%.
[0021] Specifically, the protective atmosphere condition described in step 4 is a vacuum or reducing atmosphere; the heat treatment process is: heating to 200-500°C at a heating rate of 1-10°C / min, and keeping warm for 0-1h; then heating to 900-1100°C at a heating rate of 5-10°C / min, and keeping warm for 0.5-2.5h for high temperature heat treatment.
[0022] The wall thickness of the high-gradient porous metal film prepared by the invention is 0.5-3 mm, and the average pore diameter is 0.19-2.1 μm.
[0023] The present invention provides a method for preparing a high-gradient porous metal film, which is prepared by using metal powder as raw material through sol-gel coating process, isostatic pressing, mold forming and high-temperature sintering process. The metal film material consists of a metal outer film, an internal supporting metal film tube and a metal transition bonding layer. The internal supporting metal film tube has a certain mechanical strength. A metal transition bonding layer is added between the metal outer film blank and the internal supporting film tube. After high-temperature sintering treatment, the low-melting-point metal powder is melted and wrapped with the high-melting-point metal powder, thereby further enhancing the bonding force between the metal film layers. The preparation method is simple, easy to operate and has a high yield rate.
[0024] Compared with the traditional powder sintered metal film material (directly brushing or plugging the surface of the metal support to add a transition layer), the metal film material provided by the present invention has a higher pore gradient and mechanical strength. In addition, the metal film material has high surface flatness, high filtration accuracy, uniform pore size distribution, and good permeability, and has broad application prospects in the field of filtration and separation technology.
[0025] The beneficial effects of the present invention are as follows:
[0026] (1) The present invention adopts a mold forming process, and uses a soft rubber sleeve and a quartz tube as an outer mold to successively prepare an internal support metal film tube and a metal outer film blank; then the internal support metal film tube is placed in a quartz tube mold with a metal outer film blank, and metal powder or metal powder coating slurry as a transition bonding layer is added to the cavity formed by the inner wall of the metal outer film blank and the outer wall of the internal support metal film tube. Under high temperature conditions, the two metal powders of different particle sizes in the transition bonding layer are mutually bonded and diffused with the internal support metal film tube and the metal outer film blank, and the bonding strength between the film layers is high; the internal support metal film tube and the quartz tube play a good positioning role for the metal powder of the transition bonding layer, which is conducive to the formation of a uniform metal film layer; the prepared porous metal film has a high pore gradient, high mechanical strength and a complete film layer.
[0027] (2) The high-gradient metal film of the present invention is composed of a metal outer film, a metal transition bonding layer and an internal supporting metal film tube. Compared with the traditional powder sintered metal film material (directly brushing or plugging the surface of the metal support to add a transition layer), the metal film material has a higher pore gradient and mechanical strength.
[0028] (3) The present invention adopts isostatic pressing to press the membrane embryo during the preparation process, which can improve the bonding force between the membrane particles, avoid void defects in the membrane, and improve the strength of the membrane and the smoothness of the surface.
[0029] (4) The present invention achieves effective bonding between the metal outer membrane and the internal supporting metal membrane tube by filling a transition bonding layer between the porous metal outer membrane blank and the internal supporting metal membrane tube, and utilizing the melting diffusion bonding of low melting point metal powder. The transition bonding layer is composed of two metal powders or metal powder slurries of different particle sizes, and the metal powder with a small particle size is consistent with the material and particle size of the metal powder used to prepare the porous metal outer membrane blank, which can reduce the difference in thermal coefficients and is beneficial to the connection between the outer membrane porous metal outer membrane blank and the internal supporting metal membrane tube; in addition, during sintering, the metal powder with a small particle size has a low melting temperature, and melts and wraps the metal powder with a large particle size, while reducing the sintering temperature, so that the metal powder of the transition bonding layer can be smoothly stored in the pores of the internal supporting metal membrane tube, and effectively bonded with the internal supporting metal membrane tube with a large particle size, and the bonding force between the membrane layers is high, so that a porous metal membrane with a high gradient is prepared.
[0030] (5) The high-gradient metal membrane tube prepared by the present invention has a smooth surface, no defects, high filtration accuracy, high mechanical strength, and uniform pore size distribution, and is suitable for the filtration process of complex systems.
[0031] (6) The high-gradient metal film preparation process provided by the present invention is simple, does not require complex equipment, has low production costs, and is easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a sample picture of a high gradient metal film tube.
[0033] Figure 2 This is the SEM image of the sample surface in Example 1.
[0034] Figure 3 This is the SEM image of the cross section of the sample in Example 1.
[0035] Figure 4 The surface and cross-section SEM images of the sample in comparative example 1 are shown.
[0036] Figure 5 This is the cracking diagram of the sample film layer of Comparative Example 2. DETAILED DESCRIPTION
[0037] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.
[0038] Example 1
[0039] Step 1: prepare a soft rubber sleeve, put the soft rubber sleeve into a quartz tube 1 with an inner diameter of 8 mm and a plugging piece at the bottom, form a cavity 1 between the outer wall of the soft rubber sleeve and the inner wall of the quartz tube 1, fill the cavity 1 with stainless steel powder A with an average particle size of 50 μm, first package, and then perform isostatic pressing, wherein the isostatic pressing pressure is 100 MPa, and the pressure is maintained for 300 seconds; finally, sinter at 1200°C under vacuum atmosphere conditions, and keep warm for 5 hours to prepare an internal support metal film tube with a wall thickness of 0.26 mm and a porosity of 40%;
[0040] Step 2: Stainless steel powder with an average particle size of 1 μm is used as a raw material, and a carboxymethyl cellulose solution with a mass fraction of 3% is added, and a sol coating liquid B is prepared according to a mass ratio of 2:1 between the stainless steel powder and the carboxymethyl cellulose solution. The sol coating liquid is first coated on the inner wall of a quartz tube 2 with an inner diameter of 10 mm, and after drying, a porous metal outer film blank B is obtained, and then the porous metal outer film blank B is packaged and subjected to isostatic pressing treatment, the treatment pressure is 150 MPa, and the pressure is maintained for 300 seconds;
[0041] Step 3: Place the internal support metal film tube prepared in step 1 into the porous metal outer film blank B that has been isostatically pressed in step 2, and set a plugging piece at one end of the porous metal outer film blank B, forming a cavity 2 between the outer wall of the internal support metal film tube and the inner wall of the porous metal outer film blank B, and fill the cavity 2 with metal powder C (wherein the metal powder C is composed of two stainless steel powders with different particle sizes, with an average particle size of 1 μm and an average particle size of 5 μm, mixed in a mass ratio of 1:1.) and set another plugging piece at the other end of the porous metal outer film blank to form a high gradient porous metal membrane assembly blank;
[0042] Step 4: Heat the high gradient metal membrane assembly embryo prepared in step 3 to 500°C at a heating rate of 5°C / min under vacuum atmosphere and keep it warm for 0.5h; then heat it to 1000°C at a heating rate of 10°C / min and keep it warm for 1h to obtain a high gradient porous metal membrane.
[0043] The high gradient porous metal membrane prepared in this embodiment has a thickness of 0.71 mm, wherein the thickness of the porous metal outer membrane B is 0.05 mm, and the average pore size is 0.19 μm.
[0044] Example 2
[0045] Step 1: prepare a soft rubber sleeve, put the soft rubber sleeve into a quartz tube 1 with an inner diameter of 18 mm and a plugging piece at the bottom, form a cavity 1 between the outer wall of the soft rubber sleeve and the inner wall of the quartz tube 1, fill the cavity 1 with nickel alloy powder A with an average particle size of 100 μm, first package, and then perform isostatic pressing, wherein the isostatic pressing pressure is 300 MPa and the pressure is maintained for 0 seconds; finally, sinter at 1250° C. under reducing atmosphere conditions and keep warm for 3 hours to prepare an internal support metal film tube with a wall thickness of 1 mm and a porosity of 30%;
[0046] Step 2: nickel alloy powder with an average particle size of 3 μm is used as a raw material, and a 1% mass fraction of hydroxyethyl methylcellulose solution is added, and a sol coating liquid B is prepared according to a mass ratio of nickel alloy powder to hydroxyethyl methylcellulose solution of 1:1. The sol coating liquid is first coated on the inner wall of a quartz tube 2 with an inner diameter of 20 mm, and then dried to obtain a porous metal outer film blank B, and then the porous metal outer film blank B is packaged and subjected to isostatic pressing treatment, the treatment pressure is 100 MPa, and the pressure is maintained for 60 seconds;
[0047] Step 3: Place the internal support metal film tube prepared in step 1 into the porous metal outer film blank B that has been isostatically pressed in step 2, and set a plugging piece at one end of the porous metal outer film blank B, forming a cavity 2 between the outer wall of the internal support metal film tube and the inner wall of the porous metal outer film blank B, and fill the cavity 2 with metal powder C (wherein the metal powder C is composed of two nickel alloy powders with different particle sizes, with an average particle size of 3 μm and an average particle size of 8 μm, mixed in a mass ratio of 0.2:1.) and set another plugging piece at the other end of the porous metal outer film blank to form a high gradient porous metal film assembly blank;
[0048] Step 4: Heat the high gradient metal membrane assembly embryo prepared in step 3 to 200°C at a heating rate of 1°C / min under reducing atmosphere conditions and keep it warm for 1 hour; then heat it to 900°C at a heating rate of 5°C / min and keep it warm for 2.5 hours to obtain a high gradient porous metal membrane.
[0049] The high gradient porous metal membrane successfully prepared in this embodiment has a thickness of 1.5 mm, wherein the thickness of the porous metal outer membrane B is 0.21 mm, and the average pore size is 0.28 μm.
[0050] Example 3
[0051] Step 1: prepare a soft rubber sleeve, put the soft rubber sleeve into a quartz tube 1 with an inner diameter of 46.5 mm and a plugging piece at the bottom, form a cavity 1 between the outer wall of the soft rubber sleeve and the inner wall of the quartz tube 1, fill the cavity 1 with titanium alloy powder A with an average particle size of 200 μm, first package, and then perform isostatic pressing, wherein the isostatic pressing pressure is 200 MPa and the pressure is maintained for 3600 seconds; finally, sinter at 1400°C under vacuum atmosphere conditions and keep warm for 0.5 hours to prepare an internal support metal film tube with a wall thickness of 2 mm and a porosity of 50%;
[0052] Step 2: titanium alloy powder with an average particle size of 20 μm is used as a raw material, and a polyacrylic acid lactone solution with a mass fraction of 5% is added, and a sol coating liquid B is prepared according to a mass ratio of 6:1 between the titanium alloy powder and the polyacrylic acid lactone solution. The sol coating liquid is first coated on the inner wall of a quartz tube 2 with an inner diameter of 50 mm, and after drying, a porous metal outer film blank B is obtained, and then the porous metal outer film blank B is packaged and subjected to isostatic pressing treatment, the treatment pressure is 200 MPa, and the pressure is maintained for 3600 seconds;
[0053] Step 3: Place the internal support metal film tube prepared in step 1 into the porous metal outer film blank B that has been isostatically pressed in step 2, and set a plugging piece at one end of the porous metal outer film blank B, forming a cavity 2 between the outer wall of the internal support metal film tube and the inner wall of the porous metal outer film blank B, and fill the cavity 2 with metal powder C (wherein the metal powder C is composed of two titanium alloy powders with different particle sizes, with an average particle size of 20 μm and an average particle size of 30 μm, mixed in a mass ratio of 3:1.) and set another plugging piece at the other end of the porous metal outer film blank to form a high gradient porous metal film assembly blank;
[0054] Step 4: Heat the high gradient metal membrane assembly embryo prepared in step 3 to 300°C at a heating rate of 2°C / min under vacuum atmosphere conditions and keep it warm for 0 hours; then heat it to 1100°C at a heating rate of 10°C / min and keep it warm for 0.5 hours to obtain a high gradient porous metal membrane.
[0055] The high gradient porous metal membrane successfully prepared in this embodiment has a thickness of 3 mm, wherein the thickness of the porous metal outer membrane B is 0.5 mm, and the average pore size is 2.1 μm.
[0056] Example 4
[0057] Step 1: prepare a soft rubber sleeve, put the soft rubber sleeve into a quartz tube 1 with an inner diameter of 28 mm and a sealing piece at the bottom, form a cavity 1 between the outer wall of the soft rubber sleeve and the inner wall of the quartz tube 1, fill the cavity 1 with stainless steel powder A with an average particle size of 150 μm, first package, and then perform isostatic pressing, wherein the isostatic pressing pressure is 160 MPa, and the pressure is maintained for 600 seconds; sinter at 1350°C under vacuum atmosphere conditions, and keep warm for 0.5 hours to prepare an internal support metal film tube with a wall thickness of 1.5 mm and a porosity of 45%.
[0058] Step 2: Stainless steel powder with an average particle size of 10 μm is used as a raw material, and a polyethylene glycol solution with a mass fraction of 2% is added, and a sol coating liquid B is prepared according to a mass ratio of 3:1 between the stainless steel powder and the polyethylene glycol solution. The sol coating liquid is first coated on the inner wall of a quartz tube 1 with an inner diameter of 30 mm, and after drying, a porous metal outer film blank B is obtained, and then the porous metal outer film blank B is packaged and subjected to isostatic pressing treatment, the treatment pressure is 150 MPa, and the pressure is maintained for 600 seconds;
[0059] Step 3: Place the internal support metal film tube prepared in step 1 into the porous metal outer film blank B that has been isostatically pressed in step 2, and set a plugging piece at one end of the porous metal outer film blank B, forming a cavity 2 between the outer wall of the internal support metal film tube and the inner wall of the porous metal outer film blank B, and fill the cavity 2 with metal powder C (wherein the metal powder C is composed of two stainless steel powders with different particle sizes, with an average particle size of 10 μm and an average particle size of 20 μm, mixed in a mass ratio of 5:1.) and set another plugging piece at the other end of the porous metal outer film blank to form a high gradient porous metal membrane assembly blank;
[0060] Step 4: Heat the high gradient metal membrane assembly embryo prepared in step 3 to 500°C at a heating rate of 3°C / min in a vacuum atmosphere and keep it warm for 3 hours; then heat it to 1050°C at a heating rate of 5°C / min and keep it warm for 1.5 hours to obtain a high gradient porous metal membrane.
[0061] The high gradient porous metal membrane successfully prepared in this embodiment has a thickness of 2.1 mm, wherein the thickness of the porous metal outer membrane B is 0.32 mm, and the average pore size is 1.2 μm.
[0062] Example 5
[0063] Step 1: prepare a soft rubber sleeve, put the soft rubber sleeve into a quartz tube 1 with an inner diameter of 10.5 mm and a plugging piece at the bottom, form a cavity 1 between the outer wall of the soft rubber sleeve and the inner wall of the quartz tube 1, fill the cavity 1 with stainless steel powder A with an average particle size of 50 μm, first package, and then perform isostatic pressing, wherein the isostatic pressing pressure is 150 MPa, and the pressure is maintained for 500 seconds; finally, sinter at 1100°C under vacuum atmosphere conditions, and keep warm for 2 hours to prepare an internal support metal film tube with a wall thickness of 0.2 mm and a porosity of 42%;
[0064] Step 2: Stainless steel powder with an average particle size of 1.5 μm is used as a raw material, and a polyethylene glycol solution with a mass fraction of 2.5% is added, and a sol coating liquid B is prepared according to a mass ratio of 0.5 between the stainless steel powder and the polyethylene glycol solution. The sol coating liquid is first coated on the inner wall of a quartz tube 2 with an inner diameter of 11 mm, and after drying, a porous metal outer film blank B is obtained, and then the porous metal outer film blank B is packaged and subjected to isostatic pressing treatment, the treatment pressure is 100 MPa, and the pressure is maintained for 300 seconds;
[0065] Step 3: Place the internal support metal film tube prepared in step 1 into the porous metal outer film blank B that has been isostatically pressed in step 2, and set a plugging piece at one end of the porous metal outer film blank B, a cavity 2 is formed between the outer wall of the internal support metal film tube and the inner wall of the porous metal outer film blank B, and the cavity 2 is filled with a coating slurry prepared by mixing metal powder C and 1% methyl cellulose solution in a mass ratio of 1:1 (wherein the metal powder C is composed of two stainless steel powders with different particle sizes, with an average particle size of 1.5 μm and an average particle size of 6 μm, mixed in a mass ratio of 0.5;) and set another plugging piece at the other end of the porous metal outer film blank, thereby forming a high-gradient porous metal membrane assembly blank;
[0066] Step 4: Heat the high gradient metal membrane assembly embryo prepared in step 3 to 500°C at a heating rate of 5°C / min under vacuum atmosphere and keep it warm for 0.5h; then heat it to 1000°C at a heating rate of 10°C / min and keep it warm for 1h to obtain a high gradient porous metal membrane.
[0067] The high gradient porous metal membrane prepared in this embodiment has a thickness of 0.5 mm, wherein the thickness of the porous metal outer membrane B is 0.11 mm, and the average pore size is 0.20 μm.
[0068] Example 6
[0069] This embodiment is basically the same as Embodiment 5, except that in step 1, the inner diameter of the quartz tube 1 is 49.5 mm, in step 2, the inner diameter of the quartz tube 2 is 50 mm, and in step 3, the metal powder coating slurry is prepared by mixing metal powder C and 3% polyvinyl alcohol solution in a mass ratio of 2:1 to obtain a coating slurry. The high gradient porous metal film prepared in this embodiment has a thickness of 0.5 mm, wherein the thickness of the porous metal outer membrane B is 0.11 mm, and the average pore size is 0.20 μm.
[0070] Example 7
[0071] This embodiment is basically the same as embodiment 5, and the metal powder coating slurry in step 3 is a coating slurry prepared by mixing metal powder C and 10% polyvinyl pyrrolidone (PVP) solution at a mass ratio of 3:1. The thickness of the high gradient porous metal film prepared in this embodiment is 0.51 mm, wherein the thickness of the porous metal outer film B is 0.11 mm, and the average pore size is 0.20 μm.
[0072] Comparative Example 1
[0073] This comparative example provides a method for preparing a metal film, which is basically the same as Example 2, except that the surface of the metal film tube prepared in step 1 is directly filled with nickel alloy powder with an average particle size of 3 μm, and finally a high-temperature heat treatment is performed to prepare the metal film. The surface uniformity of the prepared metal film layer is poor, the yield is low, and the small-particle metal powder enters the pores of the metal film tube. The surface and cross-section SEM images of the sample prepared in this comparative example 1 are as follows: Figure 4 As shown, large holes appear on the surface of the membrane layer, and the pore size is relatively large; from the cross-sectional SEM, it can be seen that the filled metal powder enters the pores of the large-diameter metal membrane tube.
[0074] Comparative Example 2
[0075] This comparative example provides a method for preparing a metal film, which is basically the same as Example 1, except that a stainless steel powder with an average particle size of 5 μm and a carboxymethyl cellulose solution with a mass fraction of 3% are first prepared in a 2:1 ratio to form a sol coating liquid, and the surface of the metal film tube prepared in step 1 is coated, and after drying, a metal film embryo 1 is obtained, and then a stainless steel powder with an average particle size of 1 μm and a carboxymethyl cellulose solution with a mass fraction of 3% are prepared in a 1:1 ratio to form a sol coating liquid, and the surface of the metal film embryo 1 is coated, and finally a high-temperature heat treatment is performed to prepare a metal film. The metal film prepared in this comparative example is prone to cracking, shedding, and peeling, and has a low yield. The cracking of the film layer is shown in the figure below. Figure 5 shown.
[0076] The samples of Examples 1 to 7 and Comparative Examples 1 and 2 were tested for pore size, bubble point and flux using a bubble point method aperture analyzer, and their surface and cross-sectional structures were tested using a scanning electron microscope.
[0077] The following table shows the average pore size, bubble point and flux data of Examples 1 to 7 and Comparative Examples 1 and 2.
[0078]
[0079] Comparing Examples 1 to 7 with Comparative Example 1, we can see that in Comparative Example 1, small-particle metal powder is directly filled on the surface of the metal support film tube to prepare the gradient metal film. Since the pore size of the metal support film tube is relatively large, the small-particle metal powder is easy to enter the pores of the support film tube. At the same time, the surface uniformity of the prepared metal film layer is poor, the film layer is prone to hole defects, and the yield is low.
[0080] Comparing Examples 1 to 7 with Comparative Example 2, we can see that in Comparative Example 2, a gradient metal film is prepared by directly coating the transition layer on the surface of the metal support film tube. The surface of the prepared metal film is prone to cracking, peeling, and shedding, and the yield is low.
[0081] From the results of the above examples and comparative examples, it can be seen that:
[0082] 1. By adopting a mold forming process, the prepared porous metal support membrane tube with large particle size is first used as an internal support, and then a transition bonding layer composed of two metal powders or metal powder slurries with different particle sizes is added between the cavity formed by the porous metal outer membrane embryo and the porous internal support metal membrane tube. By adding a transition bonding layer in the cavity, it can play a buffering and fixing role, and promote the bonding between metal powders of different particle sizes. Among them, the small-particle metal powder in the transition bonding layer is consistent with the porous metal outer membrane powder, which can effectively avoid the difference in thermal coefficient. During high-temperature heat treatment, the small-particle metal powder with a low melting point is melted and melted and bonded with the metal powder particles on the surface of the porous metal outer membrane embryo and the porous internal support metal membrane tube, so as to achieve high-strength bonding between the membrane layers.
[0083] 2. The preparation process of the present invention does not require brushing or plugging operations on the surface of the support to add a transition layer, which can effectively reduce mass transfer resistance and improve the pore gradient and filtration accuracy of the metal membrane.
[0084] 3. The present invention uses quartz tubes and soft rubber sleeves as molds to assist molding. On the one hand, they play a role in fixing and assisting molding. On the other hand, they can reduce the fluidity of metal powder during sintering, improve the film-forming properties of the film layer, and ensure the repeatability and yield rate of high-gradient metal films. Sintering of metal powder will cause sintering shrinkage. The above-mentioned sintering process can keep the position of the metal powder relatively fixed, so the pore size distribution is uniform, making the metal film layer have better permeability.
[0085] 4. The present invention adopts isostatic pressing to press the film embryo during the preparation process, which can improve the bonding force between the film particles, and improve the strength of the film and the smoothness of the surface while avoiding void defects in the film.
[0086] 5. The porous metal membrane prepared by the present invention has high pore gradient, high filtration accuracy, high mechanical strength and good permeability.
[0087] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a high gradient porous metal membrane, characterized in that: The high gradient porous metal film is prepared from metal powder as raw material through sol coating process, isostatic pressing, mold forming and high temperature sintering process. The specific steps are as follows: Step 1: prepare a soft rubber sleeve, put the soft rubber sleeve into a quartz tube 1 with a plugging piece at the bottom, form a cavity 1 between the outer wall of the soft rubber sleeve and the inner wall of the quartz tube 1, fill the cavity 1 with metal powder A, and after packaging and isostatic pressing, perform high-temperature heat treatment to prepare an internal support metal film tube; Step 2: Using metal powder B as a raw material, mix it with organic additive 1 in proportion to prepare sol coating liquid B, first apply the sol coating liquid B on the inner wall of quartz tube 2 to obtain porous metal outer film blank B after drying, and then package the porous metal outer film blank B and perform isostatic pressing treatment; Step 3: Place the internal support metal film tube prepared in step 1 into the porous metal outer film blank B that has been isostatically pressed in step 2, and set a plugging piece at one end of the porous metal outer film blank B, forming a cavity 2 between the outer wall of the internal support metal film tube and the inner wall of the porous metal outer film blank B, fill the cavity 2 with metal powder C or metal powder C coating slurry, and set another plugging piece at the other end of the porous metal outer film blank B, thereby forming a high-gradient porous metal film assembly blank; Step 4: The high gradient metal membrane assembly embryo prepared in step 3 is subjected to heat treatment under protective atmosphere conditions to obtain a high gradient porous metal membrane.
2. The method for preparing a high gradient porous metal membrane according to claim 1, characterized in that: The metal powder A described in step 1 is stainless steel powder, nickel alloy powder or titanium alloy powder with an average particle size of 50 to 200 μm; the inner diameter of the quartz tube 1 is 8 to 49.5 mm.
3. The method for preparing a high gradient porous metal membrane according to claim 1, characterized in that: The isostatic pressing pressure in step 1 is 100-300 MPa, and the holding time is 0-3600 s; the high temperature heat treatment is carried out under vacuum or reducing atmosphere at 1100-1400° C. for 0.5-5 h.
4. The method for preparing a high gradient porous metal membrane according to claim 1, characterized in that: The material of the metal powder B described in step 2 is stainless steel powder, nickel alloy powder or titanium alloy powder; the average particle size of the metal powder B is in the range of 1 to 20 μm.
5. The method for preparing a high gradient porous metal membrane according to claim 1, characterized in that: The organic additive 1 described in step 2 is a mixed solution of an organic additive and water; the organic additive is hydroxyethyl methyl cellulose, carboxymethyl cellulose, polyacrylic acid lactone or polyethylene glycol; the mass fraction of the organic additive in the organic additive 1 is 1% to 5%.
6. The method for preparing a high gradient porous metal membrane according to claim 1, characterized in that: The mass ratio of the metal powder B to the organic additive 1 in step 2 is (0.5-6):1; the inner diameter of the quartz tube 2 is 10-50 mm; the pressure of the isostatic pressing treatment is 100-300 MPa, and the holding time is 0-3600 s.
7. The method for preparing a high gradient porous metal membrane according to claim 1, characterized in that: The metal powder C described in step 3 is mixed by metal powder B and metal powder D in a mass ratio of (0.2 to 5): 1; the average particle size of the metal powder D is 5 to 30 μm; the materials of the metal powder B and metal powder D are both stainless steel powder, nickel alloy powder or titanium alloy powder; the average particle size of the metal powder B is 1 to 20 μm.
8. The method for preparing a high gradient porous metal membrane according to claim 1, characterized in that: The metal powder C coating slurry described in step 3 is a coating slurry obtained by mixing metal powder C and organic additive 2 in a mass ratio of (1 to 3): 1; the organic additive 2 is a mixture of polyvinyl alcohol, methyl cellulose or polyvinyl pyrrolidone and water; the mass fraction of the organic additive in the organic additive 2 is 1% to 10%.
9. The method for preparing a high gradient porous metal membrane according to claim 1, characterized in that: The protective atmosphere condition described in step 4 is a vacuum or reducing atmosphere; the heat treatment process is: heating to 200-500°C at a heating rate of 1-10°C / min, and keeping warm for 0-1h; then heating to 900-1100°C at a heating rate of 5-10°C / min, and keeping warm for 0.5-2.5h for high temperature heat treatment.
Citation Information
Patent Citations
Method of manufacturing gradual-change bore diameter stainless steel antipriming pipe
CN101428346A
Preparation method of porous stainless steel film
CN103691329A
Preparation method of stainless steel filtering membrane pipe
CN106390763A
Method for preparing porous stainless steel film
CN109876667A